2020
DOI: 10.1155/2020/4854837
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Modeling Using Z-F Model and RSM for Flow Analysis in Z-SHAPE Ducts

Abstract: Turbulent flow in Z-shape duct configuration is investigated using Reynolds stress model (RSM) and ζ-f model and compared to experimental results. Both RSM and ζ-f models are based on steady-state RANS solutions. The focus was on regions where the RSM has over- or underpredicted the flow when compared to the experimental results and on regions where there are flow separations and high turbulence. The performance of predicting the flow reattachment length in each model is studied as well. RSM has shown the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Another turbulence model used, similar to the k-ε model, is k-ζ-f, which provides a good balance between computational cost and the accuracy of the results due to the particularities of the ζ term modeling [40]. According to [40], both RANS with RSM and the k-ζ-f model produce reasonable results with a good accuracy in resolving the dominant structures of the turbulent flow. In comparison with LES, the k-ζ-f model has a better advantage in managing computational cost efficiency, even compared with the RSM, which it is 20% faster than.…”
Section: Reynolod-average Navier-stokes Formalism and Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Another turbulence model used, similar to the k-ε model, is k-ζ-f, which provides a good balance between computational cost and the accuracy of the results due to the particularities of the ζ term modeling [40]. According to [40], both RANS with RSM and the k-ζ-f model produce reasonable results with a good accuracy in resolving the dominant structures of the turbulent flow. In comparison with LES, the k-ζ-f model has a better advantage in managing computational cost efficiency, even compared with the RSM, which it is 20% faster than.…”
Section: Reynolod-average Navier-stokes Formalism and Turbulence Modelmentioning
confidence: 99%
“…In comparison with LES, the k-ζ-f model has a better advantage in managing computational cost efficiency, even compared with the RSM, which it is 20% faster than. Regarding the two RANS models, paper [40] showed that the k-ζ-f model provides a better prediction of flow separation and reattachment. The k-ζ-f model has been developed by Hanjalic, Popovac and Hadziabdic [27].…”
Section: Reynolod-average Navier-stokes Formalism and Turbulence Modelmentioning
confidence: 99%
“…Turbulent flow in Z-shape duct configuration is investigated using Reynolds stress model (RSM) and ζ-f model and compared to experimental results [10]. Both RSM and ζ-f models are based on steady-state RANS solutions.…”
Section: Figure 1 the Uniform Velocity Profile For The Transition Bementioning
confidence: 99%